Proceedings of the 53rd Annual Meeting of the Association for Computational Linguistics and the 7th International Joint Confere 2015
DOI: 10.3115/v1/p15-2144
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of Ezafe Construction in Persian Parsing

Abstract: Ezafe construction is an idiosyncratic phenomenon in the Persian language. It is a good indicator for phrase boundaries and dependency relations but mostly does not appear in the text. In this paper, we show that adding information about Ezafe construction can give 4.6% relative improvement in dependency parsing and 9% relative improvement in shallow parsing. For evaluation purposes, Ezafe tags are manually annotated in the Persian dependency treebank. Furthermore, to be able to conduct experiments on shallow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Tables and compare those algorithms. With respect to POS tagging, the effect of FNLP‐ontology is studied on the work of Nourian et al (). The gold Ezafe tag set introduced by the authors is extremely helpful in part of semantic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tables and compare those algorithms. With respect to POS tagging, the effect of FNLP‐ontology is studied on the work of Nourian et al (). The gold Ezafe tag set introduced by the authors is extremely helpful in part of semantic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical methods annotate words, employing the tags of their neighbours and the frequency of sequences. Conditional random fields (CRFs) are also used to annotate word sequences (McCallum & Lafferty, ; Nourian, Rasooli, Imany, & Faili, ). Research has shown that the CRFs generated more fault than statistical methods in early runs, although they produced more accurate outcomes after that.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Compare Examples 5a and 5b, for instance. This means that ezafe information will help the model, and also humans, to better detect the phrase boundaries, which can be helpful in recognizing syntactic roles (Nourian et al, 2015).…”
Section: The Role Of Ezafementioning
confidence: 99%